Relationship between food choices and eating habits with nutritional status of public high school teachers - Nur Hasanah, Laras Eka; Sari, Yulia; Febrinasari, Ratih Puspita (Alma Ata University Press, 2025)
ABSTRAK Latar Belakang: Overweight merupakan kondisi terjadinya penumpukan lemak berlebih di dalam tubuh yang berisiko bagi kesehatan. Prevalensi overweight Kota Surakarta sebesar 24,03%.Menurut Riskesdas (2018), PNS, TNI, Polri, dan pegawai BUMN dan BUMD sebanyak 20% mengalami obesitas sentral, sesuai dengan data Kemenkes. Data Pokok Pendidikan (2022) menunjukkan bahwa 69,23% PNS (Pegawai Negri Sipil) adalah guru. Guru memiliki banyak pekerjaan dan merasa tertekan saat bekerja. Terlalu banyak makan adalah cara untuk mengurangi stres. Kebiasaan makan buruk yaitu terlalu banyak mengkonsumsi makanan tinggi energi, karbohidrat, lemak, rendah serat menyebabkan penambahan berat badan. Penelitian ini dilakukan untuk mengetahui hubungan pemilihan makan dan kebiasaan makan dengan status gizi guru SMA Negeri di Surakarta.Tujuan: Mengetahui hubungan pemilihan makan dan kebiasaan makan dengan status gizi pada guru di SMA Negeri Kota Surakarta..Metode: Desain penelitian Cross-Sectional. Populasi penelitian adalah guru di SMA Negeri di Surakarta dengan 96 responden. Data kebiasaan makan menggunakan kuesioner Adolescent Food Habits Checklist (AFHC), data pemilihan makan dengan kuesioner Food Choice Questionnaire (FCQ) dan status gizi dengan pengukuran antropometri. Uji statistik menggunakan uji Chi-Square.Hasil: Hasil penelitian menunjukkan bahwa guru paling banyak berstatus gizi pre-obesitas (47.9%). Hasil penelitian menunjukkan bahwa kebiasaan makan pada guru adalah makan sehat sebesar 65,2%. Guru paling banyak melakukan pemilihan makanan sesuai dengan weight control sebanyak 11 responden 23,9%. Terdapat hubungan yang bermakna antara kebiasaan makan dan pemilihan makan dengan status gizi pada guru di SMA Negeri Kota Surakarta.Kesimpulan: Terdapat hubungan yang bermakna antara kebiasaan makan dan pemilihan makan dengan status gizi, hal ini bisa disebabkan karena kebiasaan makan yang tidak sesuai pedoman gizi seimbang merupakan penyebab utama kelebihan berat. KATA KUNCI: pemilihan makan ; kebiasaan makan ; status gizi ; guru ABSTRACTBackground: Overweight is a condition of excessive fat accumulation in the body that is risky for health. According to Riskesdas (2018), civil servants, TNI, Polri, and employees of BUMN and BUMD as much as 20% have central obesity, in accordance with data from the Ministry of Health. Basic Education Data (2022) shows that 69.23% of civil servants are teachers. Teachers have a lot of work and feel stressed Background: Overweight is a condition of excessive fat accumulation in the body that is risky for health. According to Riskesdas (2018), civil servants, TNI, Polri, and employees of BUMN and BUMD as much as 20% have central obesity, in accordance with data from the Ministry of Health. Basic Education Data (2022) shows that 69.23% of civil servants are teachers. Teachers have a lot of work and feel stressed at work. Overeating is a way to reduce stress. Bad eating habits that consume too much food high in energy, carbohydrates, fat, low in fiber cause weight gain. This study was conducted to determine the relationship of food selection and eating habits with the nutritional status of public high school teachers in Surakarta.Objectives: To determine the relationship between food selection and eating habits with nutritional status among teachers in public high schools in Surakarta City.Methods: Cross-Sectional research design. The study population was teachers in public high schools in Surakarta with 96 respondents. Data on eating habits using the Adolescent Food Habits Checklist (AFHC) questionnaire, food selection data with the Food Choice Questionnaire (FCQ) and nutritional status with anthropometric measurements. Statistical test using Chi-Square test.Results: The results showed that most teachers had pre-obese nutritional status (47.9%). The results showed that the eating habits of teachers were healthy eating by 65.2%. Most teachers make food choices in accordance with weight control as many as 11 respondents 23.9%. There is a significant relationship between eating habits and food selection with nutritional status in teachers in public high schools in Surakarta.Conclusions: There is a significant relationship between eating habits and food selection with nutritional status, this can be due to eating habits that are not in accordance with balanced nutritional guidelines are the main cause of overweight..KEYWORD: food selection ; eating habits ; nutritional status ; teachers Received: 31 July 2024; Revised: 22 Apr 2024; Accepted: 14 Jan 2025; Available online: 30 Mar 2025; Published: 30 Mar 2025